Postural correlates with painful situations - Lelard, Thierry; Montalan, Benoit; Morel, Maria F.; Krystkowiak, Pierre; Ahmaidi, Said; Godefroy, Olivier; Mouras, Harold (Frontiers in Human Neuroscience, 2013)
Background: Emotional context may play a crucial role in movement production. According to simulation theories, emotional states affect motor systems. The aim of this study was to compare postural responses assessed by posturography and electromyography when subjects were instructed to imagine themselves in a painful or a non-painful situation. Methods: Twenty-nine subjects (22.3 ± 3.7 years) participated in this study. While standing quietly on a posturographic platform, they were instructed to imagine themselves in a painful or non-painful situation. Displacement of the centre of pressure (COP), leg muscle electromyographic activity, heart rate, and electrodermal activity were assessed in response to painful and non-painful situations. Results:The anteroposterior path was shorter (p<0.05) when subjects imagined themselves in a painful situation (M = 148.0 ± 33.4 mm) compared to a non-painful situation (158.2 ± 38.7 mm). Higher Tibialis Anterior (TA) activity (RMS-TA = 3.38 ± 1.95 % vs 3.24 ± 1.85 %; p < 0.001) and higher variability of Soleus (SO) activity (variation coefficient of RMS-SO = 13.5 ± 16.2 % vs M = 9.0% ± 7.2 %; p<0.05) were also observed in painful compared to non-painful situations. No significant changes were observed for other physiological data Conclusion: This study demonstrates that simulation of painful situations induces changes in postural control and leg muscle activation compared to non-painful situations, as increased stiffness was demonstrated in response to aversive pictures in accordance with previous results.